2017
DOI: 10.21475/ajcs.17.11.10.pne592
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum (Sorghum bicolor) physiology and phytomass in saline-sodic soil treated with amendments and single superphosphate

Abstract: This study aimed to evaluate the physiology and phytomass accumulation of sorghum plants, in saline-sodic soil treated with amendments and doses of single superphosphate. The experiment was conducted in the period from January to June 2013, in a greenhouse in the municipality of Pombal, Paraíba, Brazil, using samples of a saline-sodic soil. The experimental design was randomized blocks, in a 2 x 5 factorial scheme, relative to two types of amendments of sodic soil and 5 levels of single superphosphate, with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Larceda et al (2006), evaluating the interaction between salinity and phosphorus in forage sorghum plants, found that the optimum level of the nutrient for this species, in the absence of salt stress, can be toxic to it under salt stress conditions. However, some authors point out that increasing the doses of phosphorus (Sá et al, 2017) and potassium (Gurgel et al, 2010) brings benefits to the physiological responses and phytomass accumulation of species such as sweet sorghum and melon, respectively. This denotes that this characteristic can be variable depending on the species, variety and nutrient involved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larceda et al (2006), evaluating the interaction between salinity and phosphorus in forage sorghum plants, found that the optimum level of the nutrient for this species, in the absence of salt stress, can be toxic to it under salt stress conditions. However, some authors point out that increasing the doses of phosphorus (Sá et al, 2017) and potassium (Gurgel et al, 2010) brings benefits to the physiological responses and phytomass accumulation of species such as sweet sorghum and melon, respectively. This denotes that this characteristic can be variable depending on the species, variety and nutrient involved.…”
Section: Resultsmentioning
confidence: 99%
“…Irrigation in the semi-arid region is usually performed using saline water with high concentrations of sodium chloride salts (Medeiros et al, 2003;Sá et al, 2020). The use of saline water in agriculture poses high risks of salinization and environmental degradation of soils, since salinity is an environmental stress that limits crop yield, particularly in arid and semi-arid regions (Praxedes et al, 2010;Sá et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation